Programma: 14 juni Joan Armatrading; 16 juni Gran Gran Fiesta; 17 juni That funky fat booty P-funk party Paradiso; 18 juni Ensemble Šadiyana
Programma: 14 juni Joan Armatrading; 16 juni Gran Gran Fiesta; 17 juni That funky fat booty P-funk party Paradiso; 18 juni Ensemble Šadiyana.